CREATION OF THE «AIR PASSENGER TRANSPORTATION» DATABASE ON THE ACCESS DBMS - Musaev , Ilya; Akhmedova , Iroda (MMIT Proceedings, 2023)
This work describes the development of the Air Passenger Transportation database. The database is an important tool for airlines in improving the efficiency and quality of their work. Its use can help air carriers to reduce the time and reduce the costs of various processes that are associated with the organization of air travel. The use of databases in air transportation is an effective way to ensure more accurate and faster decision-making, increase control and management of transportation processes, improve the quality of passenger service and increase the profitability of the airline. A conceptual database model using an ER diagram has been developed. The data schema "entity - relationship" with the indication of attributes is constructed. In the Access DBMS, objects of the Main button form, several linking forms have been created, queries have been compiled in SQL, a report.